Study of endocrinal profile and trichoscopic features in female pattern hair loss at tertiary care hospital - Naik, Ravina R.; Shukla, Pankaj (International Journal of Research in Dermatology, 2022)
Background: Patterned hair loss is one of the commonest conditions for which both men and women seek dermatologist. Though term androgenetic alopecia is used synonymously for female pattern hair loss, role of androgens and other hormones in its causation remains controversial. Also, in literature few studies are present suggesting role of trichoscopy in female pattern hair loss. We sought to investigate role of endocrine disturbances and trichoscopic findings in female pattern hair loss as per Ludwig classification. Methods: This was a prospective case control study. 100 cases and 100 age matched controls were enrolled in study. Laboratory investigations were done in both groups and trichoscopic examination was done in cases, at frontal and occipital scalp. The data was analyzed using t test, McNemar test and as mean, standard deviation and as percentages. Results: The difference between the mean value of body mass index, hemoglobin, T4, prolactin, follicle stimulating hormone, testosterone and dehydroepiandrosterone were found to be statistically significant as compared to controls. On trichoscopy, hair diameter diversity was commonest findings, however focal atrichia, 2-3 hairs/hair unit, white dots, honey comb pigmentation (HCP) correlated with grade of hair loss. Conclusions: Our study supports role of hormonal disturbances in causation of female pattern hair loss and thus we recommend doing tests in early onset and severe degrees of hair loss. Though diagnosis is mainly clinical trichoscopy could be excellent tool which is simple, non-invasive and cost-effective tool and may help to differentiate Female patterned hair loss from other condition like chronic telogen effluvium.